Roald Amundsen's Belgica diary : the first scientific expedition to the Antarctic - Amundsen, Roald; Decleir, Hugo (Red.) (Bluntisham Books, 1999)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; dagbok; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Bernt Balchen : polar aviator - Glines, Carroll V (Smithsonian Institution Press, 1999)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; polarekspedisjoner; polarflyving

The effects of personality and interpersonal relations on crew performance during space simulation studies - Sandal, Gro Mjeldheim (Life Support & Biosphere Science, 1998)
There has been a substantial increase in the number of people living and operating in isolated, confined, and artificially engineered environments, such as spacecraft, deep diving, weather stations, submarines, and polar outposts. This article gives an overview of research undertaken in a variety of extreme environments in an effort to better understand how semiautonomous, task-oriented groups operating within these environments develop over time, as well as identification of the individual characteristics that promote performance under such circumstances. Research reviewed includes space simulation studies for the European Space Agency (ESA) where groups were isolated in hyperbaric chambers, as well as findings from polar expeditions, space missions, submarine missions, and other military settings. Findings from the space simulation studies in hyperbaric chambers provided empirical evidence for interpersonal issues anecdotally reported in Antarctica and in other isolated, operational team environments, such as "scapegoating" of deviant crew members, displacement of aggression to outside personnel, and time patterns in psychological reactions. No indications of a "psychological limit" for how long people can tolerate remaining in isolation and confinement were found. Certain personality characteristics were consistently associated with coping, and individuals characterized by strong achievement motivation combined with interpersonal sensitivity seemed to adapt better than others. Together, these results have implications for selection and training of people operating within extreme environments.
Keywords: Antarktis; polarekspedisjoner; polarforskere; polarområdene; psykologi

Expedition photography in polar areas - Barr, Susan (Photoresearcher, 1997)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; fotografi; historie; polarekspedisjoner; polarområdene

Belgica-ekspedisjonen : et hundreårsminne - Lie, Svein B (Norvegiana Nytt, 1997)
Keywords: Antarktis; Belgica ekspedisjon; forskning; oppdagelsesreiser; polarekspedisjoner

The South Pole - Mountfield, David (A history of polar exploration, 1974)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; Sørpolen; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner

Byrd's South Pole Flight - 1929-30 - Isakson, Evelyn Moore (Bernt Balchen, colonel, United states Air force, retired : a special report on the unique career of a great American patriot, 1972)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; polarekspedisjoner; polarflyving

Saga of the white horizon - Olsen, Magnus L (Nautical Publishing Co., 1972)
Keywords: Antarktis; Lincoln Ellsworth; ekspedisjoner; oppdagelsesreiser; polarekspedisjoner; transantarktiske flyturen

Ashore on the continent - Quartermain, L B (South to the Pole : the early history of the Ross Sea sector, Antarctica, 1967)
Keywords: Antarctic (skip); Antarktis; Carsten Egeberg Borchgrevink; Henrik Johan Bull; Rosshavet; første landgang; oppdagelsesreiser; polarekspedisjoner

The first settlers - Quartermain, L B (South to the Pole : the early history of the Ross Sea sector, Antarctica, 1967)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; biologi; ekspedisjonen; geologi; meteorologi; overvintring; polarekspedisjoner

General report of the expedition - Giæver, John; Schytt, Valter; Hisdal, Vidar (Geology, biology & general report of the expedition, 1963)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geologi; glasiologi; meteorologi; polarekspedisjoner; seismologi; topografi

Samer i polarforskningen - Nissen, Kristian (Sameliv : Samisk selskaps årbok, 1963)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; ekspedisjonen; ekspedisjoner; forskning; første landgang; oppdagelsesreiser; overvintring; polarekspedisjoner; samer

U južnogo poljusa god 1900 - Borchgrevink, Carsten Egeberg (1958)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Hitch your wagon : the story of Bernt Balchen - Knight, Clayton; Durham, Robert C (Bell, 1950)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; polarekspedisjoner; polarflyving

Captain Amundsen's expedition, 1910-1912 - Hayes, James Gordon (Antarctica : a treatise on the southern continent, 1928)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; polarekspedisjoner

Das Festland am Sydpol : die Expedititon zum Sydpolarland in den Jahren 1898-1900 - Borchgrevink, Carsten Egeberg (Schottlaender, 1905)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Magnetic and meteorological observations made by the "Southern Cross" Antarctic expedition 1898-1900 - Borchgrevink, Carsten Egeberg; Bernacchi, Louis (Royal Society of London, 1902)
Keywords: Antarktis; Southern Cross; ekspedisjonen; ekspedisjoner; forskning; magnetisme; meteorologi; observasjoner; oppdagelsesreiser; polarekspedisjoner